Investigating atmospheric instabilities posing threat to maritime navigation by means of Q-vectors and frontogenetic function - Dariusz CHAŁADYNIAK; Janusz M. JASIŃSKI (Transport Problems, 2008)
Atmospheric instabilities, e.g. frontal zones with hazardous phenomena such as strong winds and intensive precipitation, pose threat to maritime activities including navigation. Capability to diagnose and forecast such processes may significantly reduce risk of casualtiesand damages to vessels or cargo. The paper presents a selected method of atmospheric instabilities analysis by means of mathematical and physical interpretation of the Q-vectors properties and their relation with the scalar frontogenetic function. A cartographic coordinatesystem for simultaneous analysis of GRID numerical data and satellite images - an aid developed for support of atmospheric instabilities investigation - is also presented.